Game Edukasi Pengenalan Negara-Negara ASEAN Untuk Siswa SMP Kelas VIII Berbasis Android - Jihan Nadila; Irfan Santiko; Retno Waluyo (Journal of Innovation Information Technology and Application (JINITA), 2021)
Technological developments are booming. Game or game use is particularly helpful in the learning process. At a time when materials are familiar with the countries of asean students will be more likely to get bored because the state map introduction, the capital and naturalness are only in the books, the need for a learning medium to be used by teachers so that students do not get bored quickly. The purpose of research is to make teachers easier in delivery of materials and easier students to study asean's introduction materials. The educational game was developed using multimedia development life cycle, as the result of the MDLC method (multimedia development life cycle), a introduction to countries in the asean program that matches the 2013 curriculum. The survey of 30 respondents scored an average of 92.19%, thereby falls into a category strongly in favor of the "educational introduction to asean state for siosswa middle school vii for android based" to be adopted as an alternative medium